Gu-Ben-Hua-Shi (AESS) formula ameliorates atopic dermatitis via regulating NLRP3 signaling pathways - Xiong Li; Luyao Feng; Tingjing Zhong; Xiumei Mo; Dong Wang; Jiangyong Gu; Dacan Chen; Xing Zeng; Fenggen Yan (Elsevier, 2023)
Background: Gu-ben-hua-shi (AESS) formula is a clinical experienced prescription from Guangdong Hospital of Traditional Chinese Medicine (TCM), which is used to treat atopic dermatitis (AD). Our previous work has shown that AESS has therapeutic effect on AD by regulating yes-associated protein (YAP). AESS formula has multi-component and multi-target characteristic, and need to be analyzed by systematic chemical profiling and network pharmacology technology, as well as verification of key signaling pathways. Therefore, this study aimed at investigating the efficacy and effect of AESS formula in the treatment of AD and its effect on NLRP3 signaling pathway. Methods: The components of AESS formula were analyzed and identified by ultra high performance liquid chromatography/tandem mass spectrometry (UHPLC- MS/MS), and the potential mechanism of AESS formula in the treatment of AD was predicted by network pharmacology approach, with detected main components, and the potential components targeted NOD-like receptor thermal protein domain associated protein (NLRP3) signaling pathway [Direct binding with NLRP3, apoptosis-associated speck-like protein (ASC) and Caspase-1] were assessed using molecular docking. AD-like symptoms were constructed by DNCB induced BALB/c mice. The effect of AESS formula on dorsal skin structure in AD-like mice was observed using H&E staining. Furthermore, the western blotting experiment explored the expression of the NLRP3 pathway protein. Results: By UHPLC-MS/MS analysis, 91 compounds were detected in AESS formula, and 76 of them were identified, while by network pharmacological analysis, 1500 component targets were obtained, and 257 of them were obtained by intersection with eczema targets. Then one of the key pathways, nucleotide-binding oligomerization domain (NOD)-like signaling pathway was obtained by KEGG enrichment analysis. Molecular docking results showed 24 main components could effectively combine with ASC and Caspase-1 (≤−7 kcal/mol). The animal experiment results further showed that AESS formula alleviates symptoms in AD-like mice. ELISA kit results showed that the expression of IL-1β and IL-18 in serum was inhibited after AESS treatment. Additionally, western blotting analysis showed that the expressions of ASC, Caspase-1 and NLRP3 protein expression in the skin tissue of mice were down-regulated after AESS treatment. The experimental results show that AESS formula inhibited the expression of NLRP3 signaling pathway for the treatment of AD. Conclusions: AESS formula can improve AD symptoms in mice by inhibiting the activation of NLRP3 inflammasome and the expression of the related downstream inflammatory cytokines.